2008
DOI: 10.1007/s10286-008-0459-y
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure changes in young male subjects exposed to a median altitude

Abstract: Our findings imply that moderate-altitude living results in a significantly greater BP and lower HR over equivalent low-altitude measurements and we conclude that chronic exposure to hypobaric hypoxia at a median altitude causes increased parasympathetic and sympathetic tone in healthy, young, Turkish males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…Studies of the effects of climate, altitude, and BP are marked by the variability of individual responses and a multitude of interacting variables. In addition to factors that affect BP independently of altitude, such as sodium intake, diet, exercise, body mass index (BMI), and age, increased altitude introduces the additional factors of hypoxia, cold, wind, altitude sickness, dehydration, and stress associated with an environmental change 1 . Interrelationships between these variables include the positive association between cold climate and increased BMI 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the effects of climate, altitude, and BP are marked by the variability of individual responses and a multitude of interacting variables. In addition to factors that affect BP independently of altitude, such as sodium intake, diet, exercise, body mass index (BMI), and age, increased altitude introduces the additional factors of hypoxia, cold, wind, altitude sickness, dehydration, and stress associated with an environmental change 1 . Interrelationships between these variables include the positive association between cold climate and increased BMI 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Mitigating some of these forces are human microenvironments that have been created to shield against some stressors. Individuals can be protected from temperature reductions of about 1°C for each 150 meters of elevation 1 with warm clothing and heated dwellings, but reduction of barometric pressure with altitude is unprotected.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with (borderline or overt) hypertension and normal subjects, increased plasma levels of epinephrine and norepinephrine following ascent to high altitude are associated with a rise in MAP (Somers et al, 1988;Palatini et al, 1989;Reeves et al, 1992;Wolfel et al, 1994;Calbet, 2003;Kara et al, 2003;Wu et al, 2007;Sizlan et al, 2008). During prolonged exposure to high altitude (months), in most (healthy) subjects, the increase in MAP subsides partially, but may not return completely to low-altitude values (Wu et al, 2007;Sizlan et al, 2008).…”
Section: Systemic Blood Pressurementioning
confidence: 93%
“…Nevertheless, in some studies, elevated systemic pressure after ascent to high altitude has been reported to be sustained for months [56]. The abovementioned studies examined BP changes at rest.…”
Section: Hypertension At High Altitudementioning
confidence: 95%